Foreshock Bubbles at Venus: Hybrid Simulations and VEX Observations. Issue 2 (22nd February 2020) - Omidi, N.; Collinson, G.; Sibeck, D.
Abstract: In the absence of a global magnetic field at Venus, its ionosphere is the obstacle to the flow of the solar wind resulting in the formation of a smaller bow shock and foreshock. Spacecraft observations and global hybrid (kinetic ions, fluid electrons) simulations have demonstrated that despite its smaller size, the foreshock at Venus has properties similar to those seen at its much larger terrestrial counterpart. This study employs global hybrid simulations and Venus Express observations to demonstrate the formation of foreshock bubbles (FBs) at Venus and examine their impacts on the Venusian ionosphere. Discovered at Earth, FBs form in response to backstreaming ion beams in the foreshock interacting with solar wind rotational or tangential discontinuities. They exhibit a hot, tenuous, and low magnetic field core bounded by a fast magnetosonic shock wave and the associated plasma sheath. Their sizes scale with the width of the foreshock and they are carried by the solar wind toward the bow shock. The results of the hybrid simulations show that despite the smaller size of the Venusian foreshock, FBs should form at this planet. A preliminary examination of the Venus Express data has shown the presence of a number of FB candidates, one of which is discussed here. Using the results of hybrid simulations we examine the impacts of FBs on the ionosphere and demonstrate their global consequences which exceed those of hot flow anomalies also formed as a result of the interaction between solar wind discontinuities and the Venusian bow shock. Key Points: Simulations show foreshock bubbles can form at Venus VEX observation show evidence for foreshock bubbles at Venus Foreshock bubbles have major impact on the Venusian ionosphere